Prospective evaluation of clinical lung ultrasonography in the diagnosis of community-acquired pneumonia in a pediatric emergency department. (February 2018) - Samson, Frédéric; Gorostiza, Iñigo; González, Andrés; Landa, María; Ruiz, Lucía; Grau, Miguel
Abstract : Objectives: To evaluate the applicability and utility of point-of-care lung ultrasonography (POCLUS) for the diagnosis of community-acquired pneumonia (CAP) in a pediatric emergency department. Methods: A prospective observational study on children with suspected CAP was carried out in a pediatric emergency department from August to December 2014. The evaluation of the chest radiography (CR) by two independent radiologists was considered as a reference standard. POCLUS was performed by pediatricians who were blinded to CR results. Following the WHO criteria, typical CAP was defined as an alveolar consolidation or infiltrate in CR and a visualization of lung consolidation with sonographic air bronchograms in POCLUS. The diagnostic accuracy of POCLUS (sensitivity, specificity, positive, and negative predictive values) was established using CR as a gold standard. Results: We enrolled 200 children with a median age of 29.5 months (interquartile range, 18.5–52.5); 58.1% were males and 42.0% had focal decreased breath sounds and/or crackles. The prevalence of typical CAP according to the radiologist's evaluation was 42.5% (end-point consolidation and/or pleural effusion 56.5%, alveolar infiltrate 43.5%). The sensitivity and specificity of POCLUS were 87.1% [95% confidence interval (CI) 78.0–93.4] and 94.8% (95% CI 89.0–98.1), respectively. The positive and negative predictive values were 92.5% (95% CI 84.4–97.2) and 90.8% (95% CI 84.2–95.3), respectively. Conclusion: POCLUS performed by an emergency pediatrician with a limited experience in ultrasonography enables the diagnosis of pneumonia with high accuracy. POCLUS could become a feasible and promising alternative to CR in the diagnosis of suspected CAP, leading to a relevant decrease in children's exposure to ionizing radiations. Further studies specifically carried out in the pediatric outpatient setting are needed.